Mechanically processing copper plate into active catalyst for electrochemical hydrogen production. (15th September 2022) - Feng, Yi; Li, Zhe; Kang, Su; Cheng, Chuan-Qi; He, Bin; Guan, Wei; Hu, Xin-Zhuo; Ji, Li-Ping; Yin, Peng-Fei; Yang, Jing; Dong, Cun-Ku; Liu, Hui; et al.
Abstract: As a cheap and earth-abundant metal, copper is known highly conductive but inactive for catalyzing hydrogen evolution reaction (HER) due to its fully filled d orbital and weak adsorption for hydrogen intermediate. Herein, we adopt a mechanical stirring process to introduce a large number of dislocations into copper plate, and retain the dislocations by the quenching effect of dry ice. Theoretical computation indicates that dislocation can cause uneven distribution of charge density, and the electron-deficient area remarkably enhances the hydrogen adsorption, turning inactive copper into active HER catalyst. The product achieves high turnover frequency, low overpotential and long-term durability. Our work bridges mechanical process and functional materials, and exploits a powerful technology on producing self-supported catalysts in a rapid way Graphical Abstract: : Image, graphical abstract